Macroeconomic Conditions and Child Schooling in Turkey - Pinar Mine Güneş; Beyza Ural Marchand (Institute of Labor Economics (IZA), 2018)
This paper examines the effects of macroeconomic shocks on child schooling in Turkey using household labor force surveys from 2005-2013. We use variation in local labor demand as an instrumental variable, particularly regional industry composition and national industry employment growth rates. The results demonstrate that child schooling is pro-cyclical in Turkey, with the most acute effects among children with less educated parents and living in rural areas. Finally, as hypothesized, we find asymmetric effects on child schooling based on skill composition of economic growth. Higher unemployment among unskilled workers increases schooling, whereas higher unemployment among skilled workers decreases schooling.
Keywords: J13; J24; O15; 330; schooling; unemployment; business cycles; Turkey